Increased Risk of Myocardial Infarction Among Patients With Type 2 Diabetes Who Carry the Common rs10830963 Variant in the MTNR1B Gene - Tan, Xiao (Diabetes Care, 2020)
OBJECTIVE: The common MTNR1B single nucleotide polymorphism rs10830963 associates with risk of type 2 diabetes (T2D). Here, we examine the association between this gene variant and the risk of myocardial infarction (MCI) among patients with T2D. MCI is a main cause of death and disability among such individuals. RESEARCH DESIGN AND METHODS: Data from the UK Biobank cohort were used in order to examine the association between rs10830963 and incidence of MCI (fatal and nonfatal) among 13,655 participants with probable T2D during a follow-up period of 6.8 years. RESULTS: Assuming an additive genetic model, a positive association was found between the rs10830963 variant in the MTNR1B gene and the risk for incident MCI during the 6.8-year follow-up (adjusted hazard ratio per G allele 1.19 [95% CI 1.02, 1.40], P = 0.03). CONCLUSIONS: The rs10830963 polymorphism may be a useful genetic marker for MCI in patients with T2D.